Economic feasibility of weed management practices in cumin (Cuminum cyminum L.) - R S Mehta, S S Meena, R K Kakani (Journal of Spices and Aromatic Crops, 2009)
Field experiments conducted at Ajmer (Rajasthan), to find out the economic feasibility ofweed management practices in terms of weed control efficiency and performance of cumin(Cuminum cyminum) indicated that weed-free treatments resulted in maximum vegetativegrowth and seed yield (6.03 q ha-1) followed by pre-emergence application of oxadiargyl @75 g ha-1 + hand weeding at 45 days after sowing (DAS). Maximum net returns (Rs. 46,365ha-1) and highest cost : benefit ratio (1:3.48) was also obtained in pre-emergence applicationof oxadiargyl @ 75 g ha-1 + hand weeding at 45 DAS.